A Versatile Strategy for Achieving Fast‐Charging Batteries via Interfacial Engineering: Pseudocapacitive Potassium Storage without Nanostructuring. Issue 27 (6th June 2022) - Kim, Seoa; Jung, Hyeonjung; Lim, Won‐Gwang; Lim, Eunho; Jo, Changshin; Lee, Kug‐Seung; Han, Jeong Woo; Lee, Jinwoo
Abstract: The rapid transport of alkali ions in electrodes is a long‐time dream for fast‐charging batteries. Though electrode nanostructuring has increased the rate‐capability, its practical use is limited because of the low tap density and severe irreversible reactions. Therefore, development of a strategy to design fast‐charging micron‐sized electrodes without nanostructuring is of significant importance. Herein, a simple and versatile strategy to accelerate the alkali ion diffusion behavior in micron‐sized electrode is reported. It is demonstrated that the diffusion rate of K + ions is significantly improved at the hetero‐interface between orthorhombic Nb2 O5 (001) and monoclinic MoO2 (110) planes. Lattice distortion at the hetero‐interface generates an inner space large enough for the facile transport of K + ions, and electron localization near oxygen‐vacant sites further enhances the ion diffusion behavior. As a result, the interfacial‐engineered micron‐sized anode material achieves an outstanding rate capability in potassium‐ion batteries (KIBs), even higher than nanostructured orthorhombic Nb2 O5  which is famous for fast‐charging electrodes. This is the first study to develop an intercalation pseudocapacitive micron‐sized anode without nanostructuring for fast‐charging and high volumetric energy density KIBs. More interestingly, this strategy is not limited to K + ion, but also applicable to Li + ion, implying the versatility of interfacial engineering for alkali ion batteries. Abstract : It is demonstrated that the diffusion rate of K + ions is significantly enhanced at the hetero‐interface between the orthorhombic Nb2 O5 (001) plane and monoclinic MoO2 (110) plane. Therefore, micron‐sized anode materials with numerous hetero‐interfaces of the orthorhombic Nb2 O5 (001) and monoclinic MoO2 (110) plane,  exhibit outstanding rate‐capability and cycle stability in potassium‐ion batteries.